Associations of Device-Measured Activity Behaviors With Health-Related Quality of Life in Patients With Metabolic Dysfunction-Associated Steatotic Liver Disease - Hadeel F. Saad; Khalid A. Alswat; Sulaiman Omer Aljaloud; Maram Alkhamash; Amani Alsadoon; Abdullah Bandar Alansare (Journal of Physical Activity and Health, 2026)
Purpose : To examine associations of device-measured activity behaviors with overall, physical, and mental health-related quality of life (HRQoL) in patients with metabolic dysfunction-associated steatotic liver disease (MASLD). Methods : This cross-sectional study included 101 patients (50.0 y, 57.43% male) with MASLD who routinely visited hepatology clinics. Participants wore wActiSleep-BT accelerometers on their nondominant wrist for 7 days to measure their sedentary behavior (in hours per day), light physical activity (PA; in minutes per day), moderate-to-vigorous PA (in minutes per day), and the Physical Activity and Sitting Time Balance Index. The Chronic Liver Disease Questionnaire for Nonalcoholic Fatty Liver Disease was utilized to assess overall, physical, and mental HRQoL. Adjusted multiple and multivariable linear regression assessed the relationships between activity behaviors and HRQoL. Results : Complex relationships were observed such that higher sedentary behavior or moderate-to-vigorous PA were independently correlated with poorer overall, physical, or mental HRQoL (beta ranged between −0.09 and −0.118, P < .05). Conversely, higher light PA was independently associated with improved overall ( β = 0.005, P = .021) and physical ( β = 0.015, P = .006) HRQoL. Physical Activity and Sitting Time Balanced Index indicated that higher total PA combined with lower sedentary behavior was correlated to enhanced physical HRQoL ( β = 0.033, P = .034). Conclusions : These findings signify the importance of incorporating activity behavior interventions in MASLD treatment strategies to enhance patient-reported outcomes, particularly HRQoL. Still, further prospective research with more robust designs and addressing the current limitations is warranted to achieve more thorough insights into the relationships between different activity behaviors and HRQoL in patients with MASLD.